2005
DOI: 10.1128/jvi.79.9.5445-5454.2005
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Equine Herpesvirus 1 as a Vector for Immunization

Abstract: Key problems using viral vectors for vaccination and gene therapy are antivector immunity, low transduction efficiencies, acute toxicity, and limited capacity to package foreign genetic information. It could be demonstrated that animal and human cells were efficiently transduced with equine herpesvirus 1 (EHV-1) reconstituted from viral DNA maintained and manipulated in Escherichia coli. Between 13 and 23% of primary human CD3 ؉ , CD4 ؉ , CD8 ؉ , CD11b ؉ , and CD19 ؉ cells and more than 70% of CD4 ؉ MT4 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…As a result of the conservative design of the dog experiment, which did not include a vector-only control, we cannot formally exclude that innate and unspecific responses not directed to H3 contribute to the protection conferred by the EHV-1 recombinant virus. Based on the notion that herpesviruses in general and EHV-1 in particular will dampen and subvert rather than induce innate responses, and based on experiments using RacH-derived modified live virus vaccines in horses, bovines and mice, we view the induction of an unspecific protective response as highly unlikely [11][12][13][14]. In addition and as discussed earlier, the rH_EIV vector induced a robust H3-specific antibody response as measured by ELISA and HI.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As a result of the conservative design of the dog experiment, which did not include a vector-only control, we cannot formally exclude that innate and unspecific responses not directed to H3 contribute to the protection conferred by the EHV-1 recombinant virus. Based on the notion that herpesviruses in general and EHV-1 in particular will dampen and subvert rather than induce innate responses, and based on experiments using RacH-derived modified live virus vaccines in horses, bovines and mice, we view the induction of an unspecific protective response as highly unlikely [11][12][13][14]. In addition and as discussed earlier, the rH_EIV vector induced a robust H3-specific antibody response as measured by ELISA and HI.…”
Section: Discussionmentioning
confidence: 87%
“…the nucleoprotein [27]. Although such a vectored combination vaccine would first need to be fully re-characterized for proper growth in vitro and expression, we do not foresee major problems since EHV-1 is known to accommodate large amounts of foreign DNA [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of expression on Hs 683 cells was particularly noteworthy, as this cell line is highly refractory to EHV-1 infection. Previous work by Trapp et al showed that EHV-1 could infect a broad array of cell lines from multiple species (25). The ability of this virus to exhibit such a broad tropism could be attributed to its use of the MHC-I receptor, which is expressed on most cell types across species.…”
mentioning
confidence: 99%
“…EHV-1 is an enveloped, double-stranded DNA virus that causes upper respiratory infection in horses and in rare cases causes paralysis and abortigenic disease (1,20). While EHV-1 does not infect humans, cells obtained from a wide array of species, including humans, are readily infected in tissue culture (25). Recently, we showed that equine major histocompatibility complex class I (MHC-I) is a cellular entry receptor for EHV-1 (12).…”
mentioning
confidence: 99%